2021
DOI: 10.1186/s13046-021-02022-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: a mirrored room between tumor bulk and tumor microenvironment

Abstract: It has been well documented that the tumor microenvironment (TME) plays a key role in the promotion of drug resistance, the support of tumor progression, invasiveness, metastasis, and even the maintenance of a cancer stem-like phenotype. Here, we reviewed TME formation presenting it as a reflection of a tumor’s own organization during the different stages of tumor development. Interestingly, functionally different groups of stromal cells seem to have specific spatial distributions within the TME that change as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 107 publications
0
47
0
Order By: Relevance
“…The tumor microenvironment (TME) has a close relationship with carcinogenesis but also provides fertile ground for tumor progression and metastasis [ 1 , 2 ]. However, our knowledge of cellular composition, organization, spatial distribution, interaction, and communication is limited concerning the TME.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) has a close relationship with carcinogenesis but also provides fertile ground for tumor progression and metastasis [ 1 , 2 ]. However, our knowledge of cellular composition, organization, spatial distribution, interaction, and communication is limited concerning the TME.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment consists of the tumor cells themselves, multiple stromal cells and extracellular matrix, and is usually characterized by hypoxia, and immunosuppression (80)(81)(82). The interactions of various cells and cytokines form a complex network of mechanisms (83), and recent studies have revealed that TME is responsible for the induction of multidrug resistance in OSCC (Figure 3).…”
Section: The Tumor Microenvironment (Tme) and Cisplatin Resistance In Osccmentioning
confidence: 99%
“…Thus, intratumor heterogeneity can occur and manifest on multiple levels based on the expansion of tumor cell clones with different genetic (driver as well as passenger mutations) and epigenetic alterations (hypermethylated DNA regions, histone modifications) as well as divergent differentiation stages (CSC versus non-CSC stage). These alterations in turn essentially contribute to different metabolic requirements (dependence on glucose, lactate or glutamine) as well as phenotypic diversity within the tumor mass resulting in e.g., proliferating versus resting, sessile versus motile/invasive or therapy responsive or resistant tumor cell clones [ 35 , 36 ]. Important to note, expansion and evolution of certain tumor cell clones are highly dependent on the adjacent stroma which co-evolves with the different tumor cell clones during pancreatic tumorigenesis, applying to the primary as well as to the secondary context [ 37 , 38 ].…”
Section: Heterogeneity Of the Tumor Cell Compartment In Pdacmentioning
confidence: 99%